2015
DOI: 10.12697/akut.2015.21.05
|View full text |Cite
|
Sign up to set email alerts
|

Controlling coaches’ behaviour, psychological need thwarting, motivation and results of the volleyball competitions

Abstract: The aim of the study was to adapt and validate an Estonian version of the Sport Motivation Scale (SMS-II) [21], the Psychological Need Thwarting Scale (PNTS) [5] and Controlling Coach Behaviours Scale (CCBS) [6] in girls' volleyball domain. SMS-II, CCBS and PNTS were assessed in 298 (U-20 42%, U-16 58%) volleyball girls from several clubs who took part in U-16 and U-20 Estonian Volleyball Federation Cup in 2015. After modifying the SMS-II, CCBS and PNTS questionnaire, all reliability demonstrated good content.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Results of the study by Gillet et al [11] showed that perceived autonomy-supportive behaviour from coaches facilitated national level judokas' autonomous motivation toward their sport, and that autonomous motivation promoted judokas' situational autonomous motivation before a competition, which, in turn, positively predicted their actual sport performance. Interestingly, however, the study by Karjane and Hein [22] showed that U-20 volleyball players from the winning team perceived their coaches to exhibit higher levels of controlling behaviour (i.e., intimidation, negative conditional regard, and excessive personal control) compared with players from the losing team. Moreover, winners scored significantly higher on external regulation, i.e., the most controlled form of motivation, compared with losers.…”
Section: Introductionmentioning
confidence: 97%
“…Results of the study by Gillet et al [11] showed that perceived autonomy-supportive behaviour from coaches facilitated national level judokas' autonomous motivation toward their sport, and that autonomous motivation promoted judokas' situational autonomous motivation before a competition, which, in turn, positively predicted their actual sport performance. Interestingly, however, the study by Karjane and Hein [22] showed that U-20 volleyball players from the winning team perceived their coaches to exhibit higher levels of controlling behaviour (i.e., intimidation, negative conditional regard, and excessive personal control) compared with players from the losing team. Moreover, winners scored significantly higher on external regulation, i.e., the most controlled form of motivation, compared with losers.…”
Section: Introductionmentioning
confidence: 97%
“…The main rationale for this suggestion is that organizational stressors appear to possess many similar characteristics to the demands and constraints emanating from a person's social environment-factors which have been empirically demonstrated to predict basic psychological needs. 26,27 Furthermore, Deci and Ryan 20 suggest that in addition to social factors, personal factors such as cognitive appraisals, may also satisfy or frustrate psychological needs. It is, therefore, important that research addresses both the social and personal antecedents of need experiences.…”
Section: Introductionmentioning
confidence: 99%
“…The primary purpose of this study was to examine how athletes appraise the organizational stressors they encounter and how this relates to the satisfaction or frustration of their * In view of this evidence-based rationale 26,27 the focus of this study will be to examine the directional relationship between cognitive appraisals of organizational stressors and psychological needs. As the relationship between a person's basic needs and his or her cognitive appraisal has been tested previously, 24 this direction is not the focus of the current study.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations